Developmental trajectories of attentional control in preschool males with fragile X syndrome. (January 2015) - Tonnsen, Bridgette L.; Grefer, Marjorie L.; Hatton, Deborah D.; Roberts, Jane E.
Highlights: Few studies have examined developmental course of attention in preschoolers with FXS. Despite poorer attention overall, attentional control improved over time. Early attentional control related to broad attention behavior problems. Performance-based measures were most sensitive to developmental change. Longitudinal surveillance is important to capturing attention development in FXS. Abstract: Attention problems are among the most impairing features associated with fragile X syndrome (FXS). However, few studies have examined behavioral development of inhibitory control in very young children with FXS. We examined attentional control in 3–6 year boys with FXS using both an experimental inhibitory control paradigm and parent-report of attention problems. Study 1 examined attentional control in FXS compared to comparison groups matched on chronological and mental age. To determine the stability of impairments over time in FXS, Study 2 examined patterns of developmental change in an expanded longitudinal sample. Across studies, males with FXS demonstrated persistent impairments in inhibitory control and parent-reported attention problems. Inhibitory control was related to, but not solely driven by, lower mental age. Although parent-rated attention problems remained stable across ages, inhibitory control improved with time. Children with more severe attention problems often displayed initially poorer inhibitory control. However, these trajectories also improved more rapidly with age. Our findings indicate that despite persistent deficits in attentional control in young children with FXS, multi-method assessment can be used to capture developmental growth that should be further supported through early, targeted intervention.